The iliac and femoral vessels: dimensions and tortuosity in a South African sample. - Lunn-Collier, Robyn (Stellenbosch : Stellenbosch University, 2023)
Stellenbosch University. Faculty of Medicine and Health Sciences. Dept. of Biomedical Sciences. Anatomy and Histology. Division of Clinical Anatomy.